2018
DOI: 10.1007/s00464-018-6331-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesorectal fat area as a useful predictor of the difficulty of robotic-assisted laparoscopic total mesorectal excision for rectal cancer

Abstract: Mesorectal fat area may serve as a useful predictor of the difficulty of total mesorectal excision for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 32 publications
5
61
1
Order By: Relevance
“…The present study suggested that a long sacral length and large MFA increased the surgical duration of robotic ME, in accordance with previous results [17,18]. To our knowledge, long sacral length reflects a shallow concave sacrum that may restrict the working space and increase the dissection workload, and a large area of mesorectal fat limits the space for counter traction [17]. For these reasons, both sacral length and the MFA were independent predictors for the difficulty of robotic ME.…”
Section: Discussionsupporting
confidence: 93%
“…The present study suggested that a long sacral length and large MFA increased the surgical duration of robotic ME, in accordance with previous results [17,18]. To our knowledge, long sacral length reflects a shallow concave sacrum that may restrict the working space and increase the dissection workload, and a large area of mesorectal fat limits the space for counter traction [17]. For these reasons, both sacral length and the MFA were independent predictors for the difficulty of robotic ME.…”
Section: Discussionsupporting
confidence: 93%
“…The association between prolonged operative time and anasotmotic leak following esophagectomy, while also a novel finding, is more straightforward . Intuitively, longer operative times may frequently represent more technically challenging cases, which could inherently be expected to have an increased risk of anastomotic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, others have also reported that anatomic factors significantly influence operative time and reflect operative complexity for rectal and hepatic resections. However, Patoir et al found that surgeon characteristics and center location accounted for 32% and 29%, respectively, of operative time variation during thyroid surgery, suggesting that factors other than operative complexity may also contribute to operative time. In consideration of the above, the etiology of prolonged operative time is likely multifactorial and varies across surgical settings.…”
Section: Discussionmentioning
confidence: 99%
“…If this applies for a proctoscope, it would be consistent to find a difference also when a flexible or rigid trans-anal platform is placed and used in procedures where dissection is based on geometrical tips (the so-called O and triangle dissection planes) [5] and on a dynamic anatomic distortion made by the pneumorectum [5]. Several authors correlated the anatomical variables with surgical results, for open, robotics, laparoscopic, and TaTME dissections [8,[17][18][19][20][21][22][23][24]. In a small series of patients who underwent open surgery for low rectal tumours, no significant differences were detected between the pelvis depth of females and males.…”
Section: Discussionmentioning
confidence: 92%